Singapore : Staff Report for the 2013 Article IV Consultation. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2013)
This 2013 Article IV Consultation highlights that since the robust recovery from the global financial crisis, Singapore's growth momentum has eased and become more erratic. Growth decelerated to 1u percent in 2012 before picking up sharply in the first half of 2013. This reflects shifts in G3 (U.S., Europe, and Japan) demand and global risk appetite. At the same time, the current account surplus narrowed sharply to a still-high 18 1\2 percent of GDP in 2012. The near-term outlook is for GDP to grow by 3 1\2 percent in 2013-2014, supported by stronger demand from major advanced economies, despite some softening in regional economies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet